Influence of Working Motivation and Environment on the Employees Bureau Performance of Organization Regional Secretariat in West Sumatera - Yusnaena; Dedi Julianto; Fitri Afrima Darma Yoeni (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Putra Indonesia YPTK, 2016)
This study presents the effect of motivation and working environment to employee performance Bureau of the Regional Secretariat of the Organization of West Sumatera province. This study is a survey with a quantitative approach and the data used is primary data obtained by field survey where in total 44 respondents were directly sampled with sample collection census techniques. Hypothesis testing is done by means of multiple linear regression analysis using the three instruments consists of three sets of questionnaires to the variable, motivation, working environment and performance. Based on the results, there are conclusion can be drawn i.e. (1) Working motivation variables affect the performance of employees Organization Bureau of West Sumatera Provincial Secretariat significantly; (2) working environment variables affect the performance of employees Organization Bureau of West Sumatera Provincial Secretariat significantly; (3) Both working motivation and working environment effect on the performance of employees of the Bureau of the Regional Secretariat of the Organization of West Sumatera Province.